The Effect Of The Application Of Sociodrama Learning Methods In Maple Civics Pancasila Material On The Behavior Of Digital Citizenship Of Grade 9 Students Of Upt Smpn 21 Gresik - Nanda Pudjo Kusumo*; Rusijono Rusijono; Lamijan Hadi Susarno (Universitas Syiah Kuala, 2023)
The purpose of this article is to show the influence of sociodrama learning methods on increasing the behavior of digital citizenship of grade 9 students. This research was conducted at SMPN 21 Panceng, Gresik Regency, East Java Province. The background of this research is the rampant misuse of technology by junior high school students in Indonesia so research was carried out to find solutions using sociodrama learning methods to minimize behavior in utilizing bad technology by making Pancasila a state ideology that must be practiced its values both in real life and virtual life. This research is quantitative research with a quasi-experimental design through a control class and an experimental class. The subjects in this study amounted to 60 students who were divided into 2 classes using saturated sampling techniques. Based on the results of the study, the results of the t-test were obtained in the post-test of digital citizenship behavior of the experimental class and the control class, which was 1,002 2,002, then in decision making it can be said that h0 is accepted and h1 is rejected. The conclusion of this study is that the sociodrama learning method does not affect the behavior of students' digital citizenship in the Pancasila material maple grade 9 SMPN 21 Panceng gresik.